Evolução do cultivo de soja em terras baixas: um panorama da mecanização na visão dos produtores - (:unkn) unknown (Universidade Federal do Pampa, 2023)
It is known that soybean cultivation in recent years has shown a growing behavior in its use in succession with the production of irrigated rice in lowland areas. As a result, there are gaps both in the implementation of this succession and in its duration. Soy becomes an important ally to these production systems due to nutritional factors both for the environment (soil and weed control) and for the economic side of the property. Aiming to have an overview of the real situation of the properties in the physiographic region of the western border of Rio Grande do Sul, the present work proposes a research with the survey of general characteristics of the implantation and persistence of the succession systems of soybean with rice in lowlands, a since knowing the production deficiency gaps, you can have a better problem solving focus. A tester was developed and imposed on 10 properties that already have the system implemented. The questions involve since the beginning of the implantation, as well as the current progress of the system, correlating sowing, cultural and harvest management factors. With the results obtained, it was concluded that the gaps in the soybean-rice production system are in the phase of establishing crops and maintaining them, that is, in sowing and spraying, since the soybean harvest when detected with that of rice becomes easier due to its greater fluidity and lower depreciation of the machinery.
Keywords: Engenharia agrícola; Pesquisa agrícola; Soja; Arroz; Cultivos agrícolas; Agricultura de várzea; Agricultural engineering; Agricultural research; Soy; Rice; Agricultural crops; Floodplain agriculture; CNPQ::CIENCIAS AGRARIAS